2015
DOI: 10.1097/tp.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Membranoproliferative Glomerulonephritis Type I After Kidney Transplantation

Abstract: Patients without recurrence in the first years should expect an excellent graft survival. Nonrelated living donors should be preferred. The HLA B49 and DR4 alleles may increase the risk for recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…Increased risk with live donation has been reported in a number of studies of primary GN, and specifically in IGAN [1621], FSGS [2224] and MCGN [2528]. This is the largest study of primary GN recurrence in transplantation on the effect of living related donation.…”
Section: Discussionmentioning
confidence: 98%
“…Increased risk with live donation has been reported in a number of studies of primary GN, and specifically in IGAN [1621], FSGS [2224] and MCGN [2528]. This is the largest study of primary GN recurrence in transplantation on the effect of living related donation.…”
Section: Discussionmentioning
confidence: 98%
“…Moroni et al reported a recurrence rate of 25 % among MPGN type I patients [ 12 ]. Green et al reported a recurrence rate of only 19 %, and Braun et al reported a recurrence rate among pediatric MPGN type II patients of 43 % [ 7 , 11 ]. Thus the recurrence rate that we report is generally consistent with that reported in previous cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports, 55 % of MPGN recurrences were diagnosed within the first year of kidney transplantation. In the studies by Lorenz et al and Green et al, all cases were diagnosed within 1.2 and 2.6 years of transplantation respectively [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations